DEVELOP LINGUISTIC COMPETENCES IN FUTURE TEACHERS’ THEORETICAL ASPECTS (World Bulletin of Social Sciences, 2023)
This article provides information on the theoretical aspects of the development of linguistic competences in future teachers and the competence-based approach, the foundation and competences related to science are relevant tools in the modern world